A study on gait and muscle activation characteristics of persons with incomplete spinal cord injury with respect to age stratification - Liu, Wen; Yang, Fan; Yao, Qing; Xu, Han; Xu, Dong; Qian, Lifeng (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveTo analyze the changes in gait and muscle activation characteristics between persons with incomplete spinal cord injury (SCI) and persons without SCI with respect to age stratification, and to examine the differences between these populations.MethodsUsing the motion acquisition system and surface electromyography system, gait spatial-temporal, kinematic, dynamic parameters, and muscle activation characteristics were collected from 90 young, middle aged, and elderly persons with incomplete SCI, as well as an equivalent number of age-matched persons without SCI. The changes and differences in gait and muscle activation characteristics across age groups between these two populations were analyzed.ResultsCompared to the controls, persons with incomplete SCI of different age showed reduced walking ability, with notable differences in stance phase, swing phase, double stance, step length, stride length and velocity (P < 0.05). The swing angle of knee flexion showed an increasing trend with age, while the swing angle of ankle inversion and abduction showed a decreasing trend with age. The average center of pressure (COP) velocity increased with age among SCI persons and COP path length of young SCI persons was shorter than that in middle aged and elderly persons. Furthermore, the pressure peak and the ratio of pressure onset time also increased with age. The muscle activation parameters indicated that a positive correlation with age was observed for the average power frequency of anterior tibialis, while no regular change with age was noted for the gastrocnemius medialis.ConclusionGait function and neuromuscular control strategies in persons with incomplete SCI are affected by age. The walking ability of young SCI persons was weaker compared to middle aged and elderly SCI persons with the same level, which may be related to differences in injury mechanism and age-specific expectations of walking ability. The changes in gait strategy and muscle activation patterns in persons with incomplete SCI provide an important basis for the development of age-specific rehabilitation intervention plans.